Assessment of Self-esteem level among Women with Spontaneous Abortion - Eman Hadi Sabit, Sarab Nasr Fadhil, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The effects of spontaneous abortion, once it occurs, physically painful and psychologically. A woman can often take several weeks to a month to recover before trying again. After a failed pregnancy, women suffer from the shame of what they perceive to be their inadequacy as a woman, loving wives, and life-giver. They can even become disillusioned with their existence and feel low self-esteem the aim of the study was to assess self-esteem level among women with spontaneous abortion and find out the relationship between self-esteem level and some women’s sociodemographic and reproductive characteristics. Methodology: A non-probability selection strategy was used to select a purposive sample of 150 aborted women for a descriptive correlational study. This study started on 1st October 2022, to 25th April, 2022. The reliability of the questionnaire was achieved through a pilot study and then presented to experts to prove its validity. The data was analyzed by the application of a descriptive and inferential statistical data analysis approach. Results: It indicated that (40.7%) of women are associated with low self-esteem level (M±SD= 16.93± 6.970). Recommendation: The health care institutions should develop support plans and open a section concerned with mental health. The health staff communicates with aborted women to reduce the psychological consequences that aborted women face from abortion and make these sections specialized for psychological support for aborted women.